Effect of nanosilver mouthwash on prevention of white spot lesions in patients undergoing fixed orthodontic treatment - a randomized double-blind clinical trial - Azheen Ali; Hadi Ismail; Kawa Amin (Elsevier, 2022)
Background/purpose: The formation of white spot lesions (WSLs) around fixed orthodontic attachments is a common complication during and following fixed orthodontic treatment, marking the result of a successfully completed treatment. This double-blind, randomized clinical trial study aims to investigate the varying effects of nano-silver, chlorhexidine (CHX) or fluoride mouthwashes on WSLs. Materials and methods: Double-blind prospective randomized clinical trial, comprised of forty-two patients with mild to moderate crowding, were recruited for this study. Randomization and allocation to trial group were carried out by computer system in college of dentistry, university of Sulaimani from January 2020 to September 2020. The patients were divided into three groups (14 per group) according to the type of mouthwash used during the treatment (nano-silver, CHX or fluoride), using block randomization. The clinical examination for the presence of WSLs was recorded through visual examination of the upper and lower anterior teeth using the International Caries Detection and Assessment System (ICDAS II) score before bonding and at 30, 90 and 180 days after bonding of the upper and lower arches. Results: The total number of patients was 42 (16 males and 26 females) with a mean age of 23.02 ± 3.841 (18-37) years old, distributed into three groups of 14 patients. There is significant difference in white spot lesions formation between the three groups; the mean of WSLs in nanosilver group is lower than CHX and fluoride group in 90 and 180 days of follow-up (P < 0.05). Conclusion: Nano-silver mouthwash is more effective than CHX and fluoride mouthwash in reducing WSLs during orthodontic treatment.